An evaluation of the level of financial reporting compliance of public schools in Kwazulu-Natal - Maama, Haruna; Zungu, Amos; Oluka, Alexander Markey; Marimuthu, Ferina (REID (Research and Evaluation in Education), 2023)
The financial management and reporting practices of public schools in KwaZulu-Natal (KZN) are a matter of concern. Section 42 of the South African Schools Act (SASA) requires that the Member of the Executive Council (MECs) for Education in KZN develops financial reporting guidelines for the schools. As a result, each province in South Africa has its l financial reporting guidelines that provide a framework for schools to report their financial information accurately and transparently. However, there are concerns about the lack of financial accountability and transparency emanating from improper financial reporting on the parts of the schools. Poor reporting practices of KZN schools may lead to negative consequences such as financial mismanagement, misappropriation of funds, and inability to account for expenditures. As a result, this study examined how public ordinary schools complied with the financial reporting requirements set forth by the KZN Provincial Department of Education (PDE). The study used a content analysis method to collect data from 58 schools' yearly financial statements over a two-year period. Descriptive statistics were used to analyze the quantitative data gathered from the financial statements to assess the degree of conformity with KZN PDE financial reporting rules. The findings revealed various instances of public schools failing to follow the rules. The schools' reporting practices were particularly poor since they did not adhere to the reporting standards. The research contributes to understanding financial reporting compliance levels among schools in KZN. The study also provides recommendations to improve compliance and promote school financial accountability.